2011
DOI: 10.1002/ijc.26488
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection in women with and without cervical cancer in Tehran, Iran

Abstract: No data exist on the population prevalence of, or risk factors for, human papillomavirus (HPV) infection in Iran or the Middle East. Cervical specimens were obtained from 825 married women aged 18-59 years from the general population of Tehran, Iran and from 45 locally diagnosed invasive cervical cancers (ICC) according to the standardized protocol of the International Agency for Research on Cancer HPV Prevalence Surveys. HPV was detected and genotyped using a GP5+/6+ PCR-based assay. HPV prevalence in the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 21 publications
5
49
3
Order By: Relevance
“…These incidence rates differ from the rates reported by Darnel et al [10] which were 47.7% and 40.9% for HPV 16 and HPV 18 respectively. However, the distribution of these two HPV types in our study is quite similar to a report from Iran which showed HPV 16 and HPV18 prevalence of 60% and 22.2% respectively [23]. Similarly, the most prevalent HPV types found in a study from India were HPV 16 (66.7%) followed by HPV 18 (19.4%) [24].…”
Section: Resultssupporting
confidence: 87%
“…These incidence rates differ from the rates reported by Darnel et al [10] which were 47.7% and 40.9% for HPV 16 and HPV 18 respectively. However, the distribution of these two HPV types in our study is quite similar to a report from Iran which showed HPV 16 and HPV18 prevalence of 60% and 22.2% respectively [23]. Similarly, the most prevalent HPV types found in a study from India were HPV 16 (66.7%) followed by HPV 18 (19.4%) [24].…”
Section: Resultssupporting
confidence: 87%
“…Yuce et al (2012) reported HPV prevalence as 25.7 (Yuce et al, 2012) and Eroglu detected a positive rate of 32.5% in Kayseri (Eroglu et al, 2011). Studies from different countries which have all used PCR based methods report rates as 7.8% in Iran (Khodakarami et al, 2012), 10.3% in India (Sauvaget et al, 2011), 19.4% in Portugal (Pista et al, 2011, 35.9% in Italy (Piana et al, 2011) and 64.1% in France (Casalegno et al, 2011). There is a wide range between HPV prevalence rates.…”
Section: Discussionmentioning
confidence: 99%
“…The IARC has coordinated cervical cancer case series, cervical cancer case-control studies, and population-based HPV prevalence surveys in a large number of countries around the world (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35); also as-yet-unpublished studies from Fiji and Bhutan). The collection of samples has spanned a period of over 20 years from 1989 until 2012 and predates the introduction of HPV vaccines.…”
Section: Methodsmentioning
confidence: 99%